Isu Pengantin Lelaki Memakai Inai di Jari: Analisis Berdasarkan Mazhab Syafii dan Fatwa di Malaysia: The Issue of Grooms Wearing Henna on Their Fingers: An Analysis Based on the Syafii School and Fatwa in Malaysia - Mohd Azhar Abdullah; Irwan Mohd Subri; Muhammad Lukman Ibrahim; Muhammad Amiri Abdul Ghani (RABBANICA - Journal of Revealed Knowledge, 2023)
Grooms wearing henna on their fingers in conjunction with weddings is still practised in Malaysian society, especially among Malays and Indians. The difference in the jurisprudence of the four madhabs, especially the Syafii madhab in this issue, also affects the inconsistency of the fatwas of the states in Malaysia. Most of the scientific studies focus more on the benefits of wearing henna according to Islamic, scientific and medical perspectives. However, the study related to the basis of fiqh related to the grooms wearing henna is not detailed. This causes confusion between the prohibition of men wearing henna on their hands due to tashabbuh and women with the need to celebrate the local uruf. This study uses a qualitative methodology through content analysis to examine the views of the Syafii school of jurisprudence in accordance with the uruf in Malaysia as decreed in the states. It aims to harmonize Muslims according to the Malaysian model. The study found that in Malaysia, the Fatwa Committee of the National Council for Islamic Affairs of Malaysia has decided that henna is permitted to be worn by the groom under certain conditions. While at the state level, there is a state fatwa that prohibits henna for the groom, and there is a state fatwa that permits it. Budaya pengantin lelaki memakai inai di jari sempena perkahwinan masih diamalkan dalam masyarakat Malaysia, khususnya Melayu dan India. Kekhilafan mazhab empat, khususnya mazhab Syafii dalam isu ini turut mempengaruhi ketidakselarasan fatwa negeri-negeri di Malaysia. Kajian-kajian ilmiah lebih tertumpu kepada manfaat penggunaan inai menurut perspektif Islam, sains dan perubatan. Manakala kajian berkaitan asas fiqh berkaitan keharusan pengantin lelaki memakai inai tidak diperincikan. Hal ini menyebabkan berlaku kekeliruan antara larangan lelaki berinai di tangan kerana tashabbuh (keserupaan) dengan kaum wanita dengan keperluan meraikan uruf (kelaziman) setempat. Kajian ini menggunakan metodologi kualitatif melalui analisa kandungan yang mengkaji pandangan fiqh mazhab Syafii selaras dengan uruf di Malaysia sebagaimana difatwakan di negeri-negeri. Ia bertujuan mengharmonikan umat Islam menurut acuan negara Malaysia. Kajian mendapati di Malaysia, Jawatankuasa Fatwa Majlis Kebangsaan Bagi Hal Ehwal Islam Malaysia telah memutuskan harus berinai bagi pengantin lelaki dengan syarat tertentu. Manakala di peringkat negeri, ada fatwa negeri yang mengharamkan berinai bagi pengantin lelaki dan ada fatwa negeri yang mengharuskannya.